2013
DOI: 10.1074/jbc.m113.495150
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin 1 Is Inactivated Due to Oxidation Induced by Peroxiredoxin under Oxidative Stress and Reactivated by the Glutaredoxin System

Abstract: Background:The Cys-62/Cys-69 dithiol of Trx1 is predicted to have a profound effect on cell signaling. Results: The Cys-62/Cys-69 dithiol of Trx1 was oxidized by Prx1, and this disulfide was reduced by the GSH/glutaredoxin system. Conclusion: Trx1 is involved in redox regulation via reversible oxidation of the Cys-62/Cys-69 dithiol of Trx1. Significance: We demonstrated the critical role of Trx1 oxidation in cell signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 51 publications
3
92
0
2
Order By: Relevance
“…In the intracellular compartment, TRX-1 was mainly present as nonfully oxidized forms in basal conditions. In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status.…”
Section: Discussionsupporting
confidence: 45%
“…In the intracellular compartment, TRX-1 was mainly present as nonfully oxidized forms in basal conditions. In this respect, there have been previous papers showing only the reduced form of TRX-1 in basal conditions [24,[42][43][44][45], while others also ͳͳ showed the two bands observed in the present paper [46,47]. Technical questions and/or culture conditions could account for these potential discrepancies since it has been demonstrated that proliferative status [48] or ion composition [49] could modify TRX-1 oxidative status.…”
Section: Discussionsupporting
confidence: 45%
“…The redox state of Trx was detected using a modified Western blot analysis [37]. Briefly, Jurkat For the determination of Prx3 redox state, after incubation with 1 (50µM) and 2 (15 µM) for 18 h, Jurkat cells were collected, centrifuged at 500 g for 5 min, washed with cold PBS and then treated with 1 mL of 10% trichloro-acetic acid.…”
mentioning
confidence: 99%
“…The neglect of alternative H 2 O 2 sinks is a conservative assumption with respect to the H 2 O 2 attained in the cytoplasm. Third, it neglects thioredoxin oxidation, as the redox capacity of most cells is sufficient to keep thioredoxin reduced in absence of strong oxidative stress [16,44,40,18]. Fourth, it accounts for a single 2-Cys peroxiredoxin whose concentration represents the sum of PrxI and PrxII, the two 2-Cys peroxiredoxins that are abundant in the cytoplasm of most mammalian cells [11].…”
Section: Models and Methodsmentioning
confidence: 99%